Work-life Balance among Nurses in a Medical Institute of National Importance: Exploring Relevant Work and Family Factors - Santhosh, Lissa; S. K. Pillai, Jawahar; Mishra, Siddharth (International Journal of Nursing Research, 2023)
Aim: This study explores what factors at work and home/family influence work-life balance among nurses at a tertiary care medical institute of national importance. Methodology: A preliminary focused group discussion was done with a representative sample to identify what work and family factors are considered significant by nurses. From these, six themes in work environment and six themes in Home/Family environment emerged. Using these themes, a questionnaire was developed for the final study. It contained questions to evaluate respondents’ opinions on each of the themes and they were asked to rank each factor on a 5-point Likert scale. This questionnaire was circulated among the sample that was selected by purposive sampling method. To understand if any relationship exists between these Work and Home-Family factors and Work-Life balance step-wise regression was done with the collected data. Results: The results revealed that both Work and HomeFamily factors affected work-life balance. Among the work factors, it was observed that designation, work station, shift, and workdays were relevant. Similarly, in the Home-Family environment factors such as time spent in household chores, number of children, presence of specially-abled child/elderly dependent, spouse employment status, and responsibility of household chores at home had an influence on work-life balance of the respondents. Conclusion: Both work and home/family factors had an influence on the work-life balance of the nurses. Designation, work station, shift and workdays were relevant work factors while time spent in household chores, number of children, presence of specially-abled child/elderly dependent, spouse employment status and responsibility of household chores at home were important in the home family front.